1992
DOI: 10.1097/00006842-199203000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Using daily ratings to confirm premenstrual syndrome/late luteal phase dysphoric disorder. Part I. Effects of demand characteristics and expectations.

Abstract: Daily symptom ratings were evaluated in 31 women who met DSM III-R criteria for a diagnosis of Late Luteal Phase Dysphoric Disorder (LLPDD), and 34 women who reported no premenstrual symptomatology. Women in both groups were randomly assigned to be aware or unaware of the menstrual cycle focus of the study. Results revealed a consistent pattern of cyclic effects, with higher ratings in the mid-luteal, premenstrual and menstrual phases for many symptoms. Ratings of women reporting severe symptoms were not affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 0 publications
1
25
0
1
Order By: Relevance
“…Disagreement resulted in full text article retrieval. 27 trials were retrieved in full text to confirm eligibility and 14 proved potentially eligible [9, 10,14,15,16,17,18,19,20,26,27,28,29,30]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disagreement resulted in full text article retrieval. 27 trials were retrieved in full text to confirm eligibility and 14 proved potentially eligible [9, 10,14,15,16,17,18,19,20,26,27,28,29,30]. …”
Section: Resultsmentioning
confidence: 99%
“…In one case, we could not establish that the trial was randomized [26]. In four others, we could not obtain the data needed for analyses, in particular measures of variance [27,28,29,30]. Attempts to contact authors to acquire missing data were unsuccessful.…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies indicate that women with significant premenstrual mood symptoms report life events as more stressful and/or less positive during the premenstruum than compared to the follicular phase of the menstrual cycle (Gallant et al, 1992;Woods et al, 1998), although they do not experience an increased frequency of stressful life events compared to healthy menstruating women or males (Schmidt et al, 1990;Lewis, 1995). Thus, it is the perception of events as more stressful that could render women with PMDD in a more aversive state and heighten their baseline response to the startle procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a more fine-grained analysis of the antecedents of crying in the different phases of the menstrual cycle may yield valuable information. In addition, there is a need for studies that focus 16 explicitly on the role of sociocultural factors in the association of crying to the menstrual cycle, especially cultural variations in attitudes towards menstruation. The Menstrual Attitude Questionnaire 31 , has been shown to be valuable in interpreting such cultural differences 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies in which women were not aware of being in a study on menstrual cycle effects, have shown that women are less likely to report decreased mood during the typical PMS days [13][14][15][16][17] . The same might be true for crying.…”
Section: Introductionmentioning
confidence: 99%